2014
DOI: 10.11604/pamj.2014.17.319.4268
|View full text |Cite
|
Sign up to set email alerts
|

Fentes labiopalatines dans la province du Katanga en République Démocratique du Congo: Aspects épidémiologiques, anatomocliniques et thérapeutiques

Abstract: Les fentes labiopalatines sont les malformations les plus rencontrées de la sphère orofaciale. L'objectif est de décrire le profil épidémiologique, anatomoclinique et thérapeutique des fentes labiopalatines observées dans la province minière du Katanga au sud-est de la République Démocratique du Congo. Il s'agit d'une étude transversale réalisée dans quatre institutions hospitalières de la province du Katanga dans des districts sanitaires différents (Hôpital Jason Sendwe à Lubumbashi, Hôpital Gécamines Panda à… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 23 publications
(39 reference statements)
4
8
0
Order By: Relevance
“…This observation raises relevant questions about gender differences in CLP prevalence. The predominance of the male sex in our cohort is consistent with previous ndings reported by several Congolese studies [10,12,13,19]. For example, a study conducted in Goma (DRC) revealed a male predominance of 59.2% in patients with cleft lip and palate [19].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This observation raises relevant questions about gender differences in CLP prevalence. The predominance of the male sex in our cohort is consistent with previous ndings reported by several Congolese studies [10,12,13,19]. For example, a study conducted in Goma (DRC) revealed a male predominance of 59.2% in patients with cleft lip and palate [19].…”
Section: Resultssupporting
confidence: 92%
“…The shortest stay was 1 day, and the longest stay 7 days. [12] and by Longombe and Tshimbila in Goma (DRC) nding 9.9 years [13]. The nding that almost half of our patients presented at the age of 5 years or younger highlights the importance of early detection of CLP.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…They study recorded 59, 1% of patients as female. However, this is in contrast with Longombe AO et al [14], in 2012, and Sangwa CM [11], in 2014 in Democratic Republic of Congo that reported a male predominance.…”
Section: Discussionmentioning
confidence: 71%
“…The 0 -5 age group was the most represented at 53.85%. In the Democratic Republic of Congo, Sangwa CM et al [11], in 2014, reported 62% of patients were older than 5 years with an average age of 11.8 years. A study conducted in France by Doray B et al [12], in 2012, showed that CP were diagnosed by antenatal ultrasound in 52% of cases.…”
Section: Discussionmentioning
confidence: 99%